Half of a century of St. Nikolai’s Church - Ивановић, Дарко (Sabornost - The Theological Year-book, 2013)
The City of Požarevac used to have only one church for more than seven decades within the nineteenth century. In the middle of the aforementioned century, there were a few futile attempts to build another, new church. Nevertheless, the new church was built in 1890, thanks to the financial support of archpriest Petar Šljivić, the then trnjanski parish priest who also happened to be the son of Živko Šljivić, the duke of the First Serbian Uprising. The new church was sanctified on the very day of the temple’s celebration in 1890 (may 9th according to the old julian calendar, namely may 22nd, according to the new gregorian calendar). The metropolitan of Serbia, Michael performed the sanctification by the help of Belgrade „Saint Sava“ seminary students choir. Saint Nikolai’s church was built in serbian-byzantine style, of steadfast material. There’s an isosceles cross in the church s foundation with quadrangle apses on its sides and a dome, the top of which ends in a gilt ball with a cross on it. It took the church several years to acquire the iconostasis and all the necessary church items, as well as to pay off the debts. The priests of the second, the third and the seventh brežanski parish of Požarevac used to perform the religious service in this very church’s. Throughout the first half of century, there were 16 of them there, mainly experienced ones. Their biographies have been presented in the latter part of this work.